(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2024)
This article describes the development of a theatre- and design-based Performance Lecture whose goal is to develop reflexivity around the theme of longevity and innovation in secondary and university level students. Theatre is an art form that aims at developing self-reflection and reflexivity in both audiences and participants, opening the door to reflective learning which, if combined with critical design and design fiction, offers an effective medium for addressing many dimensions of Responsible Innovation (RI). The workshop involves the presentation of a fictional “near-future” product, a drink called "Longevity". The drink contains nanobots that once ingested can be directed (with an app) to stimulate the body to produce certain compounds, allowing the user to control different properties in their blood “in flow”. This innovative use of technology offers more bodily efficiency, leading to a longer life. This methodology was primarily developed during the A Society for All Ages. Longevity-driven design Masters course at Milan Polytechnic (2022-23) and the Interaction Design and Service Design Masters courses at Milan Domus Academy (2023), and is grounded in grassroots approaches to Responsible Innovation.